(untitled) (Docentes 2.0 Journal, 2026)
Faculty digital competence has established itself as a key factor in the design of educational experiences mediated by mobile technologies in higher education, owing to its direct influence on the pedagogical integration of digital resources and on the quality of learning. In this regard, the present study aimed to analyze the relationship between faculty digital competence and educational experiences based on mobile learning (m-learning), while also considering cognitive variables associated with learning self-regulation, sustained attention, and cognitive load. The research was framed within the positivist paradigm, employing a quantitative approach and a non-experimental, correlational, and cross-sectional design based on the hypothetico-deductive method. A structured questionnaire was administered to a convenience sample of 60 university faculty members. The instrument was developed based on the DigCompEdu framework and on validated scales regarding m-learning experiences and cognitive processes; it demonstrated adequate levels of internal consistency (α = 0.81–0.93). The results revealed positive and statistically significant relationships between faculty digital competence and the quality of m-learning-based educational experiences (r > 0.60; p < 0.01), as well as significant differences based on the mode of instruction. Furthermore, exploratory regression analysis identified faculty digital competence as a significant predictor of educational experiences mediated by mobile devices, explaining a substantial proportion of the model’s variance. It is concluded that strengthening faculty digital competence is crucial for enhancing more effective, innovative, and cognitively sustainable mobile pedagogical practices within the university context, and for fostering learning environments adapted to current technological demands and to the cognitive processes involved in autonomous learning.